Understanding and Managing Freshwater Recreational Fisheries as Complex Adaptive Social-Ecological Systems. Issue 1 (2nd January 2017) - Arlinghaus, R.; Alós, J.; Beardmore, B.; Daedlow, K.; Dorow, M.; Fujitani, M.; Hühn, D.; Haider, W.; Hunt, L. M.; Johnson, B. M.; Johnston, F.; Klefoth, T.; et al.
ABSTRACT: The state of knowledge on the science and management of freshwater recreational fisheries is reviewed, with the objective of integrating insights from disparate fields such as fisheries science, environmental complexity theory, common-pool-resource theory, and resilience theory. First, freshwater recreational fisheries are characterized as complex adaptive social-ecological systems (SESs). Subsequently, two interrelated frameworks, drawing on the Ostrom framework for the analysis of SESs and adaptive management as key foundations, are presented. These frameworks are useful to structure the complexity and apprehend the various feedbacks and links inherent in any particular recreational fisheries system. Moreover, the frameworks help to identify operational management strategies in the face of substantial social-ecological uncertainty. It is concluded that to understand and manage freshwater recreational fisheries as complex adaptive SESs, a sustained shift from disciplinary to inter- and sometimes transdisciplinary research as well as a focus on flexible, adaptive and generally enabling rather than command-and-control type governance and management are needed. Understanding and managing recreational fisheries as complex adaptive SESs will benefit from an increasing focus on (i) managing social-ecological feedbacks and processes, (ii) managing critical slow variables that either drive the system or maintain it in potentially undesirable states, and (iii) managing and maintaining social and ecological diversity. It is hoped that the frameworks presented in this article may guide future interdisciplinary inquiry to manage for sustainability by building resilience.